Similarities and Differences in the Works of the Great English Writer and Journalist Jack London’s “Love Of Life” and “White Fang” - Abduolimova, Maftuna; Xolmatova, Umida (Journal of Innovation in Education and Social Research, 2024)
In the article, the two works of the great English writer Jack London, “Love of Life” and “White Fang” are classified differently. Similarities and differences betwen them are skillfully explained.